Duodenal low‐grade inflammation and expression of tight junction proteins in functional dyspepsia. Issue 10 (20th February 2019) - Taki, Masato; Oshima, Tadayuki; Li, Min; Sei, Hiroo; Tozawa, Katsuyuki; Tomita, Toshihiko; Fukui, Hirokazu; Watari, Jiro; Miwa, Hiroto
Abstract: Background: Duodenal changes in functional dyspepsia (FD) might be related to the development of symptoms. However, relationships among low‐grade inflammation, Helicobacter pylori infection, and protein expression by tight junctions (TJs) in the duodenum are unclear. We therefore aimed to determine whether duodenal inflammation and genes associated with TJ proteins are associated with FD. Methods: We evaluated inflammatory cell infiltration of the duodenum, H pylori infection, and genes associated with TJ proteins in duodenal biopsy specimens from 35 patients with FD according to the Rome III diagnostic questionnaire and from 31 asymptomatic controls without structural diseases. We immunohistochemically detected eosinophils and mast cells and counted them. The expression of claudins, occludin, and zonula occludens (ZO)‐1 mRNA was evaluated using quantitative RT‐PCR. Infection with H pylori was determined by measuring serum antibodies, rapid urease or urea breath tests, and endoscopic findings. Results: Sex, age, and H pylori infection rates did not differ between patients with FD and controls. The numbers of eosinophils and mast cells were significantly increased in patients with FD compared with controls and were significantly correlated. Inflammatory cell counts in the duodenum were not associated with H pylori infection status. Claudin‐3 mRNA expression was increased in the patients with FD. Conclusions: Subtle inflammation identified in the duodenum of patients with FD might be associated with the onset and persistence of dyspeptic symptoms. Abstract : Eosinophil and mast cell infiltration of the duodenum were significantly correlated in patients with FD. The effects of H pylori infection on eosinophil and mast cell infiltration in the duodenum did not significantly differ between patients with FD and controls.